Neutralizing Antibody Response after Intramuscular Purified Vero Cell Rabies Vaccination (PVRV) in Iranian Patients with Specific Medical Conditions - Rahimi, Pooneh (PLoS One, 2015)
OBJECTIVE: Post exposure prophylaxis using one of the WHO-approved vaccines is the method of choice for preventing rabies. Abnormal immune function in patients with some specific medical conditions, such as pregnancy, chronic hepatitis B virus infection, different types of cancers like lymphoma, diabetes I and II, corticosteroid consumption by patients with rheumatoid arthritis and lupus erythematosus, could impair the immunologic response to various vaccines. The immune response to rabies vaccination has never been examined in patients with any of these described medical conditions. This study purposed to evaluate the neutralyzing antibody response after vaccination with purified Vero cell rabies vaccine (PVRV) according to the WHO-recommended Post–Exposure Prophylaxis (PEP) "ESSEN" regimen. METHODS: Thirty healthy volunteers and 50 volunteers with different medical conditions who were exposed to a suspected rabid animal in the 2nd or 3rd category of exposure received 5 doses of PVRV under the ESSEN protocol. Three blood samples were collected on days 0 (before the first dose), 14, and 35. The anti-rabies antibody titer was measured using the Rapid Fluorescent Foci Inhibition Test (RFFIT) and an ELISA Bio-Rad, Platelia, Rabies II kit. RESULTS: All subjects reached NAb titers above 0.5 IU/ml by day 14 after vaccination. On day 35 (1 week after receiving the last rabies vaccine), anti-rabies antibodies were in the protective level (>0.5 IU/ml) in both groups. There was no statistically significant difference in anti-rabies antibody response due to the type of exposure (category 2 or 3), and successful seroconversion was confirmed in both groups. CONCLUSION: In conclusion, the ESSEN protocol using the PVRV vaccine is sufficient for rabies prophylaxis in patients with specific medical conditions.